Effect of laser energy on weld strength for neodymium yttrium aluminum garnet (ND:YAG) AT λ = 1.06 μm / Khairi Khazman Zulkiflee and Nurul Sabihah Zakaria - Zulkiflee, Khairi Khazman; Zakaria, Nurul Sabihah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
The effect of different laser welding energies on neodymium yttrium aluminium garnet was studied and discussed. Results for weld strength at 0.9 Joules, 1.0 Joules and 1.1 Joules laser energy had been investigated for the butt joint of titanium plate with 0.01-inch thickness using pull test method. The results showed that the laser energy had effect on weld strength of the welded samples. The average of weld strength results show increasing with the increasing on laser energy from 0.9 Joules, 1.0 Joules and 1.1 Joules which is 29.968 N, 32.444 N and 34.605 N respectively. Differences of laser energy influence the weld strength as higher weld strength was observed at higher laser energy. The highest weld strength observed is 36.785 N at 1.1 Joules. These results show the laser energy gives higher weld strength for titanium plate.